Managing childhood fever and pain - the comfort loop - Clinch Jacqui; Dale Stephen (BMC, 2007)
Abstract Parents can transmit their anxiety to their child, and just as children can pick up on parental anxiety, they can also respond to a parent's ability to stay calm in stressful situations. Therefore, when treating children, it is important to address parental anxiety and to improve their understanding of their child's ailment. Parental understanding and management of both pain and fever - common occurrences in childhood - is of utmost importance, not just in terms of children's health and welfare, but also in terms of reducing the economic burden of unnecessary visits to paediatric emergency departments. Allaying parental anxiety reduces the child's anxiety and creates a positive feedback loop, which ultimately affects both the child and parent. In this review, the integral role of parental perception of the child's condition and the efficacy of treatment in the management of childhood fever and pain will be discussed.